Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
Adolf Hitler (1889-1945) presents one of the most thoroughly documented cases of progressive oral disease in modern European history, remarkable not only for its clinical severity but for the extraordinary forensic consequences to which that clinical condition gave rise. By the final year of his life, Hitler retained only 4 of his natural teeth; the remainder of his dentition had been replaced by an elaborate network of gold crowns, bridges, and prosthetic elements constructed and maintained by his personal dentist, Professor Hugo Johannes Blaschke (1881-1959), a graduate of the University of Pennsylvania who served simultaneously as chief of dental services for the Waffen-SS. The oral disease responsible for this near-total loss of natural dentition encompassed chronic periodontitis, rampant caries, and periapical sepsis, significantly compounded by poor oral hygiene, a high-sugar diet, and the xerogenic effects of the polypharmacy prescribed by Hitler's personal physician, Dr. Theodor Morell. When Hitler died by suicide in the Führerbunker on April 30, 1945, the unique and easily recognizable prosthetic work of Blaschke, recovered from among the charred remains in the Reich Chancellery garden, became the primary and ultimately definitive means of identifying his body. The forensic chain that followed involved his dental assistant, Käthe Heusermann; his dental prosthetist, Fritz Echtmann; the US Army Counter-Intelligence Corps interrogation of Blaschke in 1945 to 1946; the pioneering odontological identification by Sognnaes and Strøm in 1973; and the final confirmatory biomedical analysis by Charlier and colleagues in 2018.